Chromatic diversity of art paintings under light-emitting diodes - Pinto, Paulo Daniel Araújo (2008)
The type of illumination used in museums influences critically the visual impression of art works because their appearance is determined by the spectral profile and intensity of the illumination. The aim of this work was to estimate computationally the chromatic diversity perceived by normal observers when viewing paintings under two types of white light-emitting diodes (LED). Hyperspectral images of eleven oil paintings were collected at the museum and the chromatic diversity under illuminant D65 and two white LED lights (LXHL-W02 and LXHL-W03 from the Luxeon’with CCT of 5500 K and 3300 K, respectively) was estimated by computing the representation of the paintings in the CIELAB colourvolume, segmented it into unitary cubes, and by counting the number of non-empty unitary cubes. It was found that chromatic diversity obtained with LXHL-W02 and LXHL-W03 was, on average, about 8% higher and 15% lower than with illuminant D65, respectively. The result suggests that LED light sources with high CCT may be suitable for museum illumination